2018
DOI: 10.1088/1361-6641/aaebb5
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of high-Si-content-Ge1−xy Si x Sn y /Ge1−x Sn x /Ge1−x–y Si x Sn y double heterostructure

Abstract: The optoelectronic properties of Ge 1−x−y Si x Sn y /Ge 1−x Sn x /Ge 1−x−y Si x Sn y double heterostructures pseudomorphically grown on a Ge substrate were investigated. The photoluminescence (PL) intensity of the sample with Ge 0.66 Si 0.23 Sn 0.11 cladding layers is three times larger compared to PL from structure with a Ge cladding layer, which can be attributed to higher energy band offsets at both conduction and valence band edges at the Ge 0.91 Sn 0.09 /Ge 0.66 Si 0.23 Sn 0.11 interface. The PL spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
(26 reference statements)
2
18
0
Order By: Relevance
“…Figure 4 shows the PL spectrum obtained at room temperature from the sample grown on ion-implanted Ge substrate with pre-annealing. Also, we show the PL spectrum obtained previously from the Ge 0.48 Si 0.33 Sn 0.19 (15 nm)/Ge 0.91 Sn 0.09 (15 nm)/Ge 0.48 Si 0.33 Sn 0.19 (50 nm) double heterostructure with a DSR value of 22% in all layers grown on virtual Ge (v-Ge) substrate for comparison 21) In addition, the PL spectrum obtained from a pseudomorphically grown Ge 1−x−y Si x Sn y (30 nm)/Ge 1−x Sn x (15 nm)/Ge 1−x−y Si x Sn y (30 nm) double heterostructure sample [as shown in Figs. 1(g)-1(h)] with a DSR value of 0% in all layers is also shown (dashed line).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the PL spectrum obtained at room temperature from the sample grown on ion-implanted Ge substrate with pre-annealing. Also, we show the PL spectrum obtained previously from the Ge 0.48 Si 0.33 Sn 0.19 (15 nm)/Ge 0.91 Sn 0.09 (15 nm)/Ge 0.48 Si 0.33 Sn 0.19 (50 nm) double heterostructure with a DSR value of 22% in all layers grown on virtual Ge (v-Ge) substrate for comparison 21) In addition, the PL spectrum obtained from a pseudomorphically grown Ge 1−x−y Si x Sn y (30 nm)/Ge 1−x Sn x (15 nm)/Ge 1−x−y Si x Sn y (30 nm) double heterostructure sample [as shown in Figs. 1(g)-1(h)] with a DSR value of 0% in all layers is also shown (dashed line).…”
Section: Resultsmentioning
confidence: 99%
“…We could practically confirm the improvement of the carrier confinement effect on the photoluminescence spectroscopy. 20,21) On the other hand, in our previous heterostructures, a serious problem remained toward lasing at room temperature, i.e. the indirect bandgap of the Ge 1−x Sn x layer pseudomorphically grown on a Ge substrate due to a large compressive strain.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, the PL peak position was approximately 0.64 eV. According to our previous report, 21) the positions of PL peaks related to L and Γ points for a pseudomorphic Ge 0.91 Sn 0.09 layer grown on Ge are approximately 0.60 and 0.70 eV, respectively. According to our bandgap calculation [see supplementary data SD2 (available online at stacks.iop.…”
Section: Resultsmentioning
confidence: 51%
“…In our previous study, we demonstrated the formation of Si x Ge 1−x−y Sn y /Ge 1−x Sn x /Si x Ge 1−x−y Sn y DHSs and high photoluminescence (PL) intensity of a 15 nm thick Ge 1−x Sn x active layer when carriers are sufficiently confined using the Si x Ge 1−x−y Sn y clad layer. 21) Although such results seem promising for the optoelectronic application of Ge 1−x Sn x , the issue of indirect bandgap nature of the Ge 1-x Sn x layer should be overcome. To this end, our group investigated a strain-relaxed direct-bandgap Ge 1−x Sn x on ionimplanted substrate.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6] This means that a quantum confinement structure suitable for device applications such as light-emitting diodes, semiconductor lasers, and high electron mobility transistors can be realized using only strain-free group-IV semiconductors. Several groups, including us, recently demonstrated the crystal growth of type-I band structures, specifically, Ge 1−x−y Si x Sn y /Ge junction, 7) Ge 1−x−y Si x Sn y /Ge 1−x Sn x / Ge 1−x−y Si x Sn y double heterojunctions, [8][9][10][11] and the multiquantum well. [12][13][14] They showed Ge 1−x−y Si x Sn y 's high potential for use in the cladding layers of lasers and resonant tunneling diodes.…”
Section: Introductionmentioning
confidence: 99%